2018
DOI: 10.1080/17512433.2018.1549488
|View full text |Cite
|
Sign up to set email alerts
|

Drug and therapeutics committees in Nigeria: evaluation of scope and functionality

Abstract: Introduction: Inappropriate use of medicines remains a problem, with consequences including increasing adverse drug reactions (ADRs) and prolonged hospitalizations. The Essential Medicines List and Drug and Therapeutics Committees (DTCs) are accepted initiatives to promote the rational use of medicines. However, little is known about DTC activities in Nigeria, the most populous African country. Areas covered: A cross-sectional questionnaire-based study was conducted among senior pharmacists, consultant physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 46 publications
(27 reference statements)
7
44
1
Order By: Relevance
“…A questionnaire was developed based on previous research 2,6-9. The questionnaire which was pretested consisted of five main parts of closed-ended questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A questionnaire was developed based on previous research 2,6-9. The questionnaire which was pretested consisted of five main parts of closed-ended questions.…”
Section: Methodsmentioning
confidence: 99%
“…Drug and therapeutics committees (DTCs) are presented in the hospitals to improve prescribing and dispensing processes of medicines. Their importance appears in different aspects such as drug selection process, cost-effectiveness, and control of drug losses 1,2. Altogether, DTCs have shown an important role in promoting, controlling and educating activities of rational drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Martin et al (Martin et al, 2003) and Jenkings et al (Jenkings and Barber, 2004) found in the UK that formulary decisions were based on a cluster of factors including the clinical benefits and the degree of certainty, with local knowledge also used in the UK (Martin et al, 2003;Jenkings and Barber, 2004). This is very different to the situation in some other sub-Saharan African countries where there is very variable PTC activities even among tertiary hospitals; however, this is not universal (Directorate of Pharmacy Services, 2012; Office of Director of Pharmaceutical Services (ODPS) Ministry of Health Ghana, 2015; Ashigbie et al, 2016;Mudenda et al, 2016;Fadare et al, 2018b;Anand Paramadhas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of medicines that are available in the public healthcare sector currently takes place through the National Essential Medicines List Committee (NEMLC) as well as provincial and facility based PTCs (Meyer et al, 2017;Republic of South Africa, 2018). Two essential tasks of PTCs within the public healthcare system are to develop and revise institutional STGs (usually adapted from national guidelines) and to maintain an institutional formulary, based on the national EML (Laing et al, 2001;Holloway and Green, 2003;Fadare et al, 2018b). The formulary development process follows a hierarchal approach according to the level of care, as outlined in the National PTC guidelines (South African National Department of Health, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the irrational use of medicines, and its consequences, are a growing challenge across Africa [7,35]. This has already resulted in a number of research activities including documenting the existence and functionality of drug and therapeutic committees across African countries, documenting pharmacovigilance activties among hospitals with the aim of establishing pertinent programmes to address current concerns including the over reliance on pharmaceutical companies for information on medicines [36][37][38][39][40][41], as well as the current state of antimicrobial stewardship programmes as a basis for developing programmes to improve the future use of antimicrobials in Africa given current concerns [42][43][44]. Such activities should help to reduce AMR rates, adverse drug reactions and associated increased hospitalization rates and death, and unaffordable costs of medicines among a population that predominantly pays 'out of pocket'.…”
Section: Discussionmentioning
confidence: 99%